Evaluation of the polymerase chain reaction for diagnosis of herpes simplex virus encephalitis. - Puchhammer-Stöckl, E (1993)
Cerebrospinal fluid samples from 257 patients with suspected herpes simplex virus encephalitis were prospectively analyzed by herpes simplex virus polymerase chain reaction. The polymerase chain reaction indicated herpes simplex virus encephalitis in 9 serologically proven cases and in 14 additional patients. Increased polymerase chain reaction signals were observed together with more severe neurological symptoms (P < 0.01) and within the first days of acyclovir treatment (P < 0.05).